A Stillborn Baby with Tetra-amelia Syndrome in Jember: A Case Report - Suseno, Daniel Alexander; Baswedan, Achmad Haykal; Putra, Muhamad Dwi Eka; Supriyadi, Muhammad Haikal; Pangestu, Wahyuning (Jember Medical Journal, 2024)
Tetra-amelia syndrome is a rare congenital disorder characterized by the absence of all four extremities. This extremity disorder occurs in 1 in 1,300 to 2,000 births. This condition is caused by genetic mutations in the WNT3 and RSPO2 genes. Specific risk factors for tetra-amelia syndrome remain unclear. This is also due to the lack of studies that discuss specific risk factors for tetra-amelia syndrome. In this case report, we discuss a stillborn baby with tetra-amelia syndrome to a mother with various pregnancy risk factors in Jember. This case report aims to examine the presence of several risk factors in the mother and their relationship with congenital disorders, especially tetra-amelia syndrome.